Answer:
-3x+6
Step-by-step explanation:
-3x-6(-1)
First, multiplying two negatives equals a positive: (-)×(-)=(+). Then,
multiply the numbers -3×+6×1 = -3x+6. Then, you got the answer and the answer is -3x+6
Answer:
The equation has no solutions .
Step-by-step explanation:
Given as :
<u>The linear equation is </u>
(24 -16 x) =
(18 x -27)
Or,
×24 -
× 16 x =
× 18 x -
× 27
Or,
×24 -
× 16 x =
× 18 x +
× 27
Or,
-
=
+
Or, 3 × 6 - 3 × 4 x = - 2 × 6 x + 2 × 9
Or, 18 - 12 x = - 12 x + 18
Or, 18 - 18 = - 12 x + 12 x
or, 0 = 0
∵ The linear equation has no variables , so the equation has no solution
Hence,The equation has no solutions . Answer
Answer:
Step-by-step explanation:
Vertically opposite angles are equal.
8y + 36 = 14y -24 Subtract 36 to both sides
8y = 14y - 24 - 36 Combine
8y = 14y - 60 Subtract 14y from both sides
8y - 14y = - 60
-6y = -60 Divide by - 6
-6y/-6 = -60/-6
y = 10
===========================
x +48 = 64 Subtract 48 from both sides
x +48 - 48 = 64-16
x = 16
The answer for your question is x=-1